Pengaruh Etika Kerja Islam dan Iklim Etis Terhadap Komitmen Organisasi Karyawan (Kajian Bank Syariah dan Bank Konvensional) - , Saturliana Mujiharti ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research was conducted in several Islamic (sharia) banks and conventional banks that have a national scale. The purpose of this research is to determine the extent to which Islamic work ethic and ethical climate affect employeesâ organizational commitment. Variables of this study include: organizational commitment, Islamic work ethic, and ethical climate. The hypothesis of the research are: 1). Islamic work ethics affect employees' organizational commitment and 2). Ethical climate affects employees' organizational commitment. The measurement used in the form of a questionnaire. Analysis and interpretation of data through multiple regression analysis using the tools of SPSS 16.0 for windows. Samples were taken by using the method of proportional sampling method of 47 respondents sharia banks and 52 respondents conventional banks. Results of research resulted in a conclusion that employee organizational commitment is influenced by the Islamic work ethic and ethical climate, with the resulting regression equation is Y = -0.125 + 0.389 X1 + 0.514 X2. This study produced additional results that organizational commitment among employees of both types of banks (sharia banks and conventional banks) are different, while the Islamic work ethics and ethical climate in the second type is the same bank.